EFFECT OF MODIFIED STARCH ON THE SHELF LIFE OF FROZEN FISH KAMABOKO WITH PREPARED SPINACH - Desai, A. S.; Joshi, V. R.; Pagarkar, A. U. (Journal of Indian Fisheries Association, 2015)
Fish kamaboko ·with spinach was prepared by mixing fish kamahoko vdthspinach prepared with different combinations of ordinary starch (OS) andmodified starch (MS), viz., 40:60, 50:50, 60:40, 1 00°/.) MS and I 00°/o OS. TheOil oc . products were frozen at -4 C and stored at -20 , and subJected tobiochemical (peroxide value, total titratable acidity, pH and moisture)organoleptic (appearance, taste and colour), microbiological (total platecount) and physical (folding and expressible water) tests at monthly intervals.Among the different combinations tried, it was observed that fish kamabokowith spinach prepared with 50:50 and 60:40 combinations of OS and S coube stored for six months at-20uC.Keywords: lVlodif1ed starch, ordinary starch, f1sh kamaboko, spinachproduct